Perlindungan Hukum Terhadap Kriminalisasi Jabatan Notaris Ditinjau Dari Undang-Undang Jabatan Notaris - Alvanso, Tonicca; Prasetyo, Mujiono Hafidh (Fakultas Syariah INSURI Ponorogo, 2023)
In essence, the function of the Notary's position is to provide services to the public in making authentic deeds and the Notary is not an interested part in the deed being made, but only as consolidates or records in writing a legal action from the interested parties. However, nowadays, due to increasingly complex legal issues, the position of Notary Public is often criminalized, namely appointing or making an act that was not originally a criminal act into an act that can be punished, the act in question includes the authority of the Notary position which the Notary tries to implement in accordance with statutory regulations. which applies in Indonesia. The formulation of the problem in this research is how legal protection against the criminalization of Notary authority is reviewed based on the Law on Notary Positions. The aim of this research is to analyze and describe how the legal protection of Notary's authority occurs if there is a form of criminalization of the authority of public officials reviewed based on the Law on the Position of Notaries. This type of research uses normative juridical research. The result of this discussion is that there is still a need for some form of legal protection against the criminalization of Notary's authority because in the Notary's Position Law there are no strong regulations protecting the authority of Notaries in carrying out their position if there is a conflict of regulations or interests